2019
DOI: 10.29166/siembra.v6i2.1622
|View full text |Cite
|
Sign up to set email alerts
|

Suplementación alimenticia de glutamina sobre el desempeño productivo en pollos de engorde

Abstract: El objetivo de esta investigación fue evaluar el tamaño del efecto de la suplementación de glutamina sobre el rendimiento productivo de pollos de engorde, la consistencia de su efecto y la influencia de otros factores mediante el uso de meta-análisis. Se encontró que la suplementación de glutamina favorece el aprovechamiento de nutrientes reflejado en menores valores de conversión alimenticia (calculada con ganancia de peso) 1,484 versus 1,518, y un tamaño medio de efecto de -0,031 (diferencia de medias) (P=0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The analyses showed that the effect sizes observed in the carcass yield are unrelated to the changes in performance, body composition ( Figure 4 ), or even carcass conformation ( Figure 5 ). The absence of a relationship between the carcass yield and the PFG in the study may be explained by the low variability in the carcass yield (effect size SD < 1 percent point) and the lower number of data rows available (k = 55; 30% lower sample size [ 56 , 57 ]. The carcass yield depends mainly on the relative weights of the carcass, viscera, and abdominal fat [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analyses showed that the effect sizes observed in the carcass yield are unrelated to the changes in performance, body composition ( Figure 4 ), or even carcass conformation ( Figure 5 ). The absence of a relationship between the carcass yield and the PFG in the study may be explained by the low variability in the carcass yield (effect size SD < 1 percent point) and the lower number of data rows available (k = 55; 30% lower sample size [ 56 , 57 ]. The carcass yield depends mainly on the relative weights of the carcass, viscera, and abdominal fat [ 53 ].…”
Section: Discussionmentioning
confidence: 99%